Soil organic matter quality and composition in a postfire Scotch pine forest in Tolyatti, Samara region - Maksimova, Ekaterina; Abakumov, Evgeny (Biological Communications, 2017)
Evaluation of humus accumulation and humification rates was conducted on soils affected by surface and crown fires during 2010 forest fires near Tolyatti (Samara region, Russia). Three key soil plots were studied for estimating SOM quality changes under the forest fire effect. Total carbon and nitrogen content, as well as Сhumic acids/Cfulvic acids (Cha/Cfa) ratios, were estimated to evaluate the dynamics of soil recovery. Humic acid powders were extracted from soils and analyzed by elemental composition and 13C-NMR spectroscopy to assess changes in structure and composition. The data indicate that the burning of a forest floor and humic horizon led to humus losses and decreases in total carbon stocks and content. As a result of the fires, the content of humic acids in the pyrogenic horizon increased. Greater increases in the degree of organic matter humification were observed for surface fires than for crown fires. Fire also lead to the formation of humic acids with an increased proportion of aromatic compounds than in control soils, which indicates the degradation of carboxylic and aliphatic groups of molecules under the burning effect. This corresponds well with the decrease of the proportion of hydrogen when comparing the elemental composition of burned soil with that of mature soil.